一种高电流密度下效率不降低的绿光有机电致发光器件 = High efficiency green organic light-emitting diode without roll-off under high current density - Tian, Miao-miao (2024)
为了提高有机电致发光器件(OLED)在高电流密度下的发光效率, 在以C545T掺杂Alq3为发光层的有机小分子绿光器件中的发光层与电子传输层之间插入超薄LiF绝缘层.结果表明, 器件的外量子效率随着电流密度的增加始终没有降低, 直至600 mA/cm2时达到最大值 4.79%, 是相同电流密度下的参考器件的外量子效率的7倍. In order to improve the efficiency of organic light emitting diodes (OLEDs) working at high current density, a LiF layer was inserted between emiiting layer (EML) and electron transporting layer (ETL) of a C545T:Alq3 based OLED. The external quantum efficiency (EQE) of the device increases with the increasing of the current density. When the current density is 600 mA/cm2, the maximum value of EQE is the biggest of 4.79%, seven times of the reference OLED.